Evaluation of French Language Teaching in the Analamanga Region: Current Status and Opportunities for Improvement - Andrianiaina Solo Raivo Lyh Raphaël; Andrianarimanana Jean Claude Omer; Gay Denis; Andrianjary Myriam; Rakotoson Olivia; Fidelio Arnold Ulrich; Ratiarimananjatovo Narindra; Ratsimandisa Haritiana Zo; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR-Publisher), 2024)
Education professionals are increasingly concerned about the level of French proficiency among Malagasy students. This article aims to assist teachers in refining their classroom practices to maximize outcomes. On-site observations were conducted in various public primary schools, middle schools, and high schools, including the primary schools of 67 ha Nord-Est and Antanimena Est, the middle schools of Betsimitatatra and Antanimena, as well as Lycée Moderne Ampefiloha, Lycée Analamahitsy, and Lycée Ivato. The investigation focused on two main aspects, emphasizing that the quality of teaching largely depends on the teachers' methods. The results show that half of the primary and middle school teachers lack a solid foundation in French, partly due to their initial training. Additionally, they lack suitable teaching materials, and their teaching methods lack rigor.